Avaliação do handicap em trabalhadores com perda auditiva induzida por ruído - Oliveira, Priscila Feliciano de (2007)
Introduction: Continuous exposure to loud sound pressure levels can cause noise-induced hearing loss (NHIL) and consequently affect the quality of life for these subjects. The handicap of hearing loss has a psychological effect characterized by isolation, stress, difficulties with family relationships, anxiety, sleep difficulties, less confidence and depression. Objective: This research shows the handicap of nourishing branch workers, intent juice workers and cement workers with noise induced hearing loss. Methods: An anamnese and a questionnaire of the handicap scale named Hearing Handicap Inventory for Adults (HHIA) were administered to 72 workers. The subjects were 23 to 58 years old and the mean age at which exposed to occupational noise was 14,5 years. Results: In 72 workers, 21 (29,2%) had handicap presence. The led/moderate auto-perception was shown in 10 (13,9%) workers and severe/significant was shown in 11 people (15,3%). In social/situational scale, the main complaints were using less telephone (38,9%), difficulties to hearing/understanding business colleagues (34,7%) and watching TV and listening to the radio (33,3%). In emotional scale 33,3% were irritated, 30,6% were bored of having difficulties in hearing and 27,8% were constrained or felt sad when they were presented to someone new. In audiograms analysis, the most affected frequency was in the range of 3 to 8 kHz, with worse thresholds in 4 kHz. The relationship between hearing loss and handicap presence was not shown. Conclusion: The handicap presence was observed in 29,2% and there did not appear to be a significant statistical difference between handicap and age, time of noise exposure, tinnitus, and hearing loss